Characterization and Suitability Assessment of Some Pomegranate-growing and Associated Soils of Solapur District, Maharashtra - K. Karthikeyan; Pramod Tiwary, Laxman B. Jadhao, Jagdish Prasad* (Journal of the Indian Society of Soil Science, 2019)
Four pomegranate-growing pedons (P1, P3, P5, P7) and four associated crop land (P2, P4, P6, P8) were characterized for physical and chemical properties, nutritional status of soils and leaves to compute soil-site suitability for pomegranate in Velapur, Adatmala, Bhalwani and Supli villages of Solapur district. Pedons were shallow (<50 cm) Inceptisols and Entisols underlain by weathered basalt. In general, clay content ranged from 20.47 to 51.81%. The soils had pH of 7.9 to 8.3 and were low in organic carbon (1.9 to 4.9 g kg-1). Cation exchange capacity (CEC) of soils varied from 17.3 to 30.2 cmol(p+)kg-1. Available N, P and K in pomegranate-growing and associated soils ranged from 114.3 to 142.3, 9.1 to 13.6 and 139.0 to 412.8 kg ha-1, respectively. The DTPA-Fe, Mn, Zn and Cu in pedons ranged from 12.1 to 19.6, 3.6 to 19.0, 0.19 to 1.60 and 2.2 to 4.4 mg kg-1, respectively. The concentration of total N, P and K in the leaves of pomegranate varied from 1.6 to 2.2, 0.11 to 0.20 and 0.36 to 0.63%, respectively and Fe, Mn, Zn and Cu content ranged from 47.2 to 68.9, 7.8 to 9.8, 1.8 to 7.9, 5.1 to 7.4 mg kg-1, respectively. The pedon P1, P2, P3 and P4 were moderately suitable whereas P5, P6, P7 and P8 were marginally suitable for pomegranate but with the application of improved agro-managements through fertigation farmers are able to get higher productivity.